Pendampingan Musik Tradisional Bersama Sanggar Musik Lupa Susah Masyarakat Kampung Bogenga Kabupaten Ngada dalam Menyongsong Pentas Musik Inklusi - Hermania Bupu; Dedy Setyawan; Ferdinandus Bate Dopo; Perseveranda Putra Korsini; Ronaldo Stainlaus Dora dampur; Vincencio Appaula Rivaldo Bata; Inosensius Liko Lewa (Rengganis Jurnal Pengabdian Masyarakat, 2026)
This community service activity aimed to provide intensive mentoring for the Lupa Susah Music Studio in Bogenga Village, Ngada Regency, East Nusa Tenggara, in preparation for an inclusive music performance involving diverse community groups, including audiences with disabilities. The studio is an arts community that preserves and develops traditional Ngada music through local instruments, including traditional drums, bamboo-based bowed instruments, and acoustic guitars adapted to Flores musical patterns. This activity used a participatory action research approach, in which the service team acted as facilitators and co-learners throughout the mentoring process. The mentoring was carried out through three stages: needs assessment, intensive workshops on traditional instrument techniques and collaborative arrangement, and rehearsal mentoring before the performance. The results showed improvement in technical playing ability, ensemble cohesion, stage readiness, and members’ confidence to perform in a broader public space. The activity also strengthened community awareness of traditional Ngada music as a living intangible cultural heritage that can be preserved through participatory, inclusive, and community-based artistic practices.